Curriculum transformations in South Africa: some discomforting truths on interminable poverty and inequalities in schools and society - Ngobeni, Norah Risana; Chibambo, Mackenzie Ishmael; Divala, Joseph Jinja (Frontiers in Education, 2023)
In this study, we argue that the different curriculum reforms South Africa embarked on have not really helped break the existing socio-economic inequalities. Precisely, the various reforms (e.g., C2005, NCS, and CAPS) initiated by the South African government have been proved to be a flop and uninspiring considering that schools have remained spaces where inequalities, violence, vandalism, harassment, stratification, and various crimes continue to exist. Outside the schooling spaces, unemployment, poverty, xenophobia, robbery, GBVs, and different forms of crime have characterized South African society. Many educational researchers have also argued that these issues could symbolize a broken education system that is guided by shoddy policies. Accordingly, we sought to establish key issues that confront South African educational system to explain how these reproduce the apartheid-era-like inequalities. In the main, we established that neoliberal-minimalist policies have significantly influenced socio-economic inequalities in South Africa. We also established that educational researchers have failed to identify neoliberalism as the root cause of South Africa's inequalities. To achieve our goals, we utilized document analysis to explain and understand how various policies, practices, and powerful individuals have influenced these injustices. Theoretically, these debates have been guided by Paul Freire's “Critical Pedagogy” and Bourdieu's “Social-cultural Capital” mainly for their ability to illuminate power relations, exclusions, and inequalities through Symbolic Violence and depravations.